Efficacy of dietary modifications and mucosal protectors in the treatment of laryngopharyngeal reflux: a multicenter study - Gelardi, Matteo; Giancaspro, Rossana; Fiorentino, Christian; Patruno, Stefano; Marroni, Jacopo; D’Avino, Alessandro; Neri, Letizia; Cassano, Michele; Neri, Giampiero (Frontiers in Medicine, 2025)
BackgroundLaryngopharyngeal reflux (LPR) is defined as an extraesophageal reflux of gastroduodenal contents to the laryngopharynx, affecting the upper aerodigestive tract. There is currently no standardized treatment protocol for LPR. The use of proton pump inhibitors (PPIs) is widely established in common practice and derives from the standard approach of using PPIs to treat patients with gastroesophageal reflux disease (GERD). However, as PPIs may not be effective on all types of reflux, the aim of our study was to evaluate the effectiveness of dietary changes and mucosal protectants, alone or in combination, in LPR treatment.MethodsThis multicenter randomized controlled trial included 48 patients divided into three groups: dietary modifications only, mucosal protectors only, and a combination of both. The patients’ responses were assessed over 1 month using the Reflux Symptom Index (RSI) and Reflux Finding Score (RFS), along with measurements of salivary and nasal pepsin concentration and rhinomanometry.ResultsSignificant improvements were observed in RSI and RFS scores across all groups. The group receiving combined dietary modifications and mucosal protectors showed the most substantial benefits. Additionally, a notable reduction in salivary and nasal pepsin concentrations and nasal resistances was observed, particularly in patients combining dietary modifications and mucosal protectors.ConclusionThe study showed that combined dietary modifications and mucosal protects strategies effectively manage LPR symptoms, offering a potential therapeutic approach.